New replacement name for the species Scarabaeus (Scarabaeolus) nitidus Davis & Deschodt, 2015 (Coleoptera: Scarabaeidae: Scarabaeinae)—not an American pest - Davis, Adrian L.v.; Stals, Riaan; Deschodt, Christian M. (Zootaxa, 2015)
In their review of the subgenus Scarabaeus (Scarabaeolus) Balthasar, 1965 (Coleoptera: Scarabaeidae: Scarabaeinae), Deschodt et al. (2015) described seven new species from Africa. One of these was Scarabaeus (Scarabaeolus) nitidus Davis & Deschodt, known by only twelve specimens from Botswana. This new name is preoccupied by Scarabaeus nitidus Linnaeus, 1758, a fact that was overlooked. The latter species has been known as Cotinis nitida (Linnaeus) since Burmeister (1842) placed the species in his new genus Cotinis. It belongs to the subfamily Cetoniinae of Scarabaeidae, is called the Green June Beetle, and is a common pest species throughout most of the eastern United States (Goodrich 1966; Woodruff 2008).